Association between obesity and urinary albumin-creatinine ratio in the middle-aged and elderly population of Southern and Northern China: a cross-sectional study - Qin, Shan (BMJ Open, 2021)
OBJECTIVE: The relationship between obesity and albuminuria has not been clarified. This study aimed to investigate the correlation between obesity and the urinary albumin-creatinine ratio (UACR) in Southern and Northern China. DESIGN: A descriptive, cross-sectional study. SETTING: Eight regional centres in REACTION (China’s Risk Evaluation of cAncers in Chinese diabeTic Individuals, a lONgitudinal study), including Dalian, Lanzhou, Zhengzhou, Guangzhou, Guangxi, Luzhou, Shanghai and Wuhan. PARTICIPANTS: A total of 41 085 patients who were not diagnosed with chronic kidney disease (CKD) and had good compliance were selected according to the inclusion criteria. Patients who were diagnosed with CKD, who had other kidney diseases that could lead to increased urinary protein excretion, who were using angiotensin-converting-enzyme inhibitors or angiotensin II receptor blockers and whose important data were missing were excluded. RESULTS: Participants with both, central and peripheral obesity, had a higher risk of elevated UACR, even after adjusting for multiple factors (OR: 1.14, 95% CI: 1.07 to 1.12, p<0.001), and the risk of high UACR in the South was more prominent than that in the North (OR (South): 1.22, 95% CI: 1.11 to 1.34; OR (North): 1.13, 95% CI: 1.04 to 1.22, p<0.001). The risk was also elevated in the male population, hypertensive individuals, glycosylated haemoglobin (HbA1c)≥6.5% and age ≥60 years in the South. Besides the above groups, diabetes was also a risk factor for the Northern population. CONCLUSIONS: In China, people with both central and peripheral obesity are prone to a high UACR, and the southern population has a higher risk than northern population. Factors such as male sex, hypertension, HbA1c≥6.5% and an age ≥60 years are also risk factors for CKD.